Procedure for calculating the nominal power of a photovoltaic generator: Collaboration with the XXIII Peruvian Symposium on Solar Energy - Calsi Silva, Brando Xavier (2020)
The nominal power of a photovoltaic system is a useful parameter in the determination of the current state of a photovoltaic generator. In the present work, the procedure proposed by Martínez-Moreno was followed, which is based on the Osterwald model. During the application of the procedure, a hysteresis effect was observed to a different extent throughout the experimental campaign. The corrected power versus irradiance values differed during the day, even when the irradiance and temperature of the module were similar. This led to an uncertainty in the inclusion of all the data. Therefore, the addition of a filter of the data is sought in the procedure of the estimation of the nominal power, as a complement to that proposed by Martinez-Moreno in an attempt to clarify the calculation in generators that presents this non-linear behavior.